Label Halal vs Kualitas Produk dalam Keputusan Pembelian Produk Makanan di Kabupaten Malang - Nizar, Muhammad; Aini, Anifatul; Mundir, Abdillah; Syu’aibi, Moch. Muhsinin (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2023)
This study aims to determine the effect of halal labeling, brand image, service quality and price on purchasing decisions and consumer loyalty. This research uses a quantitative approach to this type of descriptive research. Data collection techniques use data through distributing questionnaires using the Google form. Data analysis uses multiple linear regression. The research findings in this study show that halal labeling has no effect on purchasing decisions for brand image, service quality and price have an effect on purchasing decisions.